Development Of Interactive Learning Media Based On Genially Website For Prehistoric Humans Material To Improve History Understanding of 10th Grade High School Student.: Pengembangan Media Pembelajaran Interaktif Berbasis Website Genially Materi Manusia Purba untuk Melatih Pemahaman Sejarah Siswa SMA Kelas X - Desy Amelia Fitri; Suroyo; Asyrul Fikri (Proram studi pendidikan Sejarah Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2025)
Cognitive processes in comprehension include interpreting, exemplifying, classifying, summarizing, concluding, comparing, and explaining. These form comprehensive cognitive abilities. This part of comprehension develops from the basic ability to transform information to the higher-level ability to analyze cause-and-effect relationships. Mastery of this entire section enables students to process information deeply and develop meaningful understanding. History learning plays an important role in raising collective awareness, creating a sense of belonging, and social solidarity. History lessons teach about the origins, development, and roles of past societies, which have the wisdom to shape students' intelligence, attitudes, and personalities. History learning still uses conventional methods such as lectures, group discussions, and simple media. More interesting and interactive learning variations are needed to train students' understanding of history through Genially website-based interactive learning media. The main objectives of developing this media are to improve students' understanding and interest in history, to provide an alternative to conventional teaching methods, and to train the digital and visual literacy skills of students at SMAN 16 Pekanbaru. The results of expert validation for the Genially website-based interactive learning media obtained a percentage of 98% from subject matter experts, 94% from media experts, and 92.3% from test students' assessments.